The C-Terminal RRM/ACT Domain Is Crucial for Fine-Tuning the Activation of ‘Long’ RelA-SpoT Homolog Enzymes by Ribosomal Complexes - Takada, Hiraku; Roghanian, Mohammad; Murina, Victoriia; Dzhygyr, Ievgen; Murayama, Rikinori; Akanuma, Genki; Atkinson, Gemma C.; Garcia-Pino, Abel; Hauryliuk, Vasili (Frontiers in Microbiology, 2020)
The (p)ppGpp-mediated stringent response is a bacterial stress response implicated in virulence and antibiotic tolerance. Both synthesis and degradation of the (p)ppGpp alarmone nucleotide are mediated by RelA-SpoT Homolog (RSH) enzymes which can be broadly divided in two classes: single-domain ‘short’ RSHs and multi-domain ‘long’ RSHs enzymes. The regulatory ACT (Aspartokinase, Chorismate mutase and TyrA) / RRM (RNA Recognition Motif) domain is a near-universal C-terminal domain of long RSHs. Deletion of RRM in both monofunctional (synthesis-only) RelA as well as bifunctional (i.e. capable of both degrading and synthesising the alarmone) Rel renders the long RSH cytotoxic due to overproduction of (p)ppGpp. To probe the molecular mechanism underlying this effect we characterised Escherichia coli RelA and Bacillus subtilis Rel RSHs lacking RRM. We demonstrate that, first, the cytotoxicity caused by the removal of RRM is counteracted by secondary mutations that disrupt the interaction of the RSH with the starved ribosomal complex – the ultimate inducer of (p)ppGpp production by RelA and Rel – and, second, that the hydrolytic activity of Rel is not abrogated in the truncated mutant. Therefore, we conclude that the overproduction of (p)ppGpp by RSHs lacking the RRM domain is not explained by lack of auto-inhibition in the absence of RRM or/and a defect in (p)ppGpp hydrolysis. Instead, we argue that it is driven by misregulation of the RSH activation by the ribosome.